Online Jihadist Propaganda Dissemination Strategies - Stuart Macdonald (2024)
It is well established that jihadist groups and their supporters post URLs on online platforms to outlink to items of propaganda stored on other platforms. Industry initiatives – such as the Global Internet Forum to Counter Terrorism’s inclusion of URLs in its hash-sharing database, and Tech Against Terrorism’s Terrorist Content Analytics Platform – have sought to counter this practice. These measures, together with new regulatory regimes and the growing use of decentralised services, raise the question whether jihadist groups’ propaganda dissemination strategies are perhaps being forced to evolve. This study considers whether there is evidence of such an evolution, by examining the means that three jihadist groups (Islamic State, Al-Qaeda and Al-Shabaab) used to disseminate their propaganda during a two-month period in early 2023. It utilises a dataset of 4,164 content-sharing posts collected from 12 channels across four different platforms: one archiving platform, one decentralised messaging service and two decentralised chat apps. Together, these posts shared a total of 796 distinct items of propaganda. The study examines how each item was shared – by outlink, inlink and/or attached to or embedded in an in-channel post – and discusses the policy implications of the findings.